Self‐Healing Magnetic Field‐Assisted Threshold Switching Device Utilizing Dual Field‐Driven Filamentary Physics - Daeyoung Chu; Donghwan Han; Sanghyun Kang; Gwon Kim; Yejoo Choi; Eungyo Jang; Changhwan Shin (Advanced Electronic Materials)
Abstract Advanced filamentary devices are crucial for developing low‐power devices to implement high‐speed logic and neuromorphic devices. Among these, HfO2‐based filamentary devices have attracted attention as viable options due to their threshold‐switching characteristics and compatibility with complementary metal‐oxide‐semiconductor (CMOS) technology. However, the unpredictability of conventional filament formation/rupture driven by an electric field challenges consistency and reliability. A paradigm shift from conventional stochastic electric field‐driven ion migration to controllable ion‐based transportation is essential to devise functional low‐power devices capable of controlling the filament process. This work introduces a magnetic field‐assisted threshold switching (MA‐TS) device, which integrates a neodymium magnet and a nickel (Ni) barrier layer to enable controlled dual field‐driven ion transportation. The dual field‐driven process combining the conventional vertical electric field‐driven ion migration with lateral magnetic field‐driven ion transportation, reveals a distinctive aspect of ion movement. The MA‐TS device achieves superior performances characterized by an ultra‐low threshold voltage (≈0 V), minimized leakage current in the off‐state, a variation‐immune hysteresis‐free characteristic, enhanced yield, and revival‐ability (i.e., self‐healing) after a failed TS operation. By overcoming the limitations of conventional filamentary devices, the MA‐TS device opens up a promising avenue for efficient and stable low‐power applications.